Economics of Improved Reproductive Performance in Dairy Cattle - Albert De Vries; Jessika van Leeuwen; William W. Thatcher (EDIS)
This fact sheet provides some estimates of the economic benefits of improved reproductive performance through increasing pregnancy rates in dairy herds. After a short literature review, the fact sheet focuses on estimates under conditions in Florida. At the herd level, the economic value of an improvement in pregnancy rate and the cost of an additional day open are estimated. This is done for both an overall increase of pregnancy rate and an increase of first service pregnancy rate. In addition, the fact sheet presents some estimates of the maximum that can be spent on a reproductive program to obtain increases in first service pregnancy rates. At the cow level, the values of a new or established pregnancy are discussed. Results show the maximum that can be spent to get specific cows pregnant. This document is AN156, one of a series of the Department of Animal Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published August 2005.